Determination of cadmium, lead and mercury residual levels in meat of canned light tuna (Katsuwonus pelamis and Thunnus albacares) and fresh little tunny (Euthynnus alletteratus) in Libya - S.K. Abolghait (Open Veterinary Journal, 2015)
Surveillance for mercury (Hg), lead (Pb) and cadmium (Cd) contamination in tuna products is crucial for consumer food safety. Hg, Pb and Cd contaminants were monitored in a total of 60 specimens of fresh little tunny (Euthynnus alletteratus) and popular brands of skipjack and yellowfin (Katsuwonus pelamis and Thunnus albacares) canned tuna commercially available in Tripoli, Libya. Direct Mercury Analyzer (DMA-80) was implemented for determination of total Hg level and graphite furnace atomic absorption spectrometry (GFAAS) was employed for determination of Cd and Pb concentrations. The results indicated that Hg had the highest concentration level and Cd had the lowest concentration level either in tested canned tuna or fresh little tunny samples. The average concentration of Hg in fresh little tunny samples was 1.185 ± 0.968 mg kg-1 wet weight (ww) and often exceeded the standard permissible limit. In addition, canned yellowfin tuna had the lowest levels of Cd (0.027 ± 0.026 mg kg-1 ww), Pb (0.075 ± 0.071) and Hg (0.163 ± 0.122 mg kg-1 ww). Results of the current surveillance indicated that canned skipjack and yellowfin tuna sold in Tripoli markets show contaminant levels well under the European thresholds adopted for Cd, Pb and Hg. However, consumption of large quantities of Mediterranean little tunny products significantly increases human exposure to the risk of Hg toxicity.